Picoeukaryotic Diversity And Activity in the Northwestern Pacific Ocean Based on rDNA and rRNA High-Throughput Sequencing - Wang, Feipeng; Xie, Yuyuan; Wu, Wenxue; Sun, Ping; Wang, Lei; Huang, Bangqin (Frontiers in Microbiology, 2019)
Picoeukaryotes play an important role in the biogenic element cycle and energy flow in oligotrophic ecosystems. However, their biodiversity and activity are less studied in open ocean systems, such as the northwestern Pacific Ocean, which is characterized by a complex hydrological setting. Here, we investigated the diversity and activity of picoeukaryotes in the northwestern Pacific Ocean using high-throughput sequencing targeting the V9 region of 18S rDNA and rRNA. Our results showed that Chlorophyta, Dinophyta, Ciliophora, MAST and Pelagophyceae were the major taxonomic groups, comprising of 77.17% and 77.53% of the total DNA and RNA sequences, respectively. In the Kuroshio Extension Current and Oyashio Current mixed waters, Chlorophyta was the dominated group in the DNA survey and Ciliophora was the dominant group in the RNA survey. Significant differences were observed in the community composition between DNA-based and RNA-based molecular approaches, and these differences were mainly attributed to Chlorophyta, Dinophyta, Ciliophora and Pelagophyceae. The average RNA: DNA ratio (i.e., relative metabolic activity) of the taxonomic groups showed that the Ciliophora species was highly active, while the Chlorophyta and Dinophyta species only had low activity. Moreover, the RNA: DNA ratios of Chlorophyta, Dinophyta, Ciliophora were significantly correlated with temperature and salinity. Overall, our study shed light on picoeukaryotic diversity and distribution in the northwestern Pacific Ocean and revealed the positive correlation between the relative metabolic activities of marine picoeukaryotes and the characteristics of water masses (e.g., temperature and salinity).